Constructing the economic–historic context of 1 Peter: Exploring a methodology - Rensburg, Fika Janse van (HTS teologiese studies, 2011)
This article explored a methodology to construct the economic–historic context of the addressees of 1 Peter, which could serve as basis for an economic interpretation of 1 Peter and other New Testament books. After discussing 1 Peter as letter, external sources were used to construct the economic–historic context of the addressees of 1 Peter. This construction was then refined utilising the letter itself, by identifying, categorising and interpreting the economically relevant portions of 1 Peter. Finally, the economic–historic context of the addressees of 1 Peter was concluded and the method summarised.